RELA promotes the progression of oral squamous cell carcinoma via TFAP2A‐Wnt/β‐catenin signaling. Issue 5 (15th February 2023) - Yang, Kaicheng; Zhao, Jianguang; Liu, Shenghui; Man, Shasha
Abstract: Oral squamous cell carcinoma (OSCC) has emerged as the most prevailing oral malignancy worldwide, characterized by cervical solid lymph node metastasis and strong local invasiveness. Overexpression of Transcription Factor AP‐2 alpha (TFAP2A) is observed in a significant proportion of OSCC cases. In this study, we aimed to elucidate the function of TFAP2A in the progression of OSCC and the related molecular signaling pathways. The role of RELA was predicted using bioinformatics analysis. The mRNA abundances of RELA, TFAP2A, and β‐catenin were assessed by Western blot and quantitative real‐timePCR. The relationship between RELA, TFAP2A, and β‐catenin and their correlation with clinicopathological characteristics of OSCC was evaluated. The target of RELA and TFAP2A was identified by the chromatin immunoprecipitation as well as luciferase reporter assay. The colony formation assay and MTS assay were performed to determine the proliferative level of OSCC cells. OSCC cell motility was determined by Transwell assay and wound‐healing assay. The protein expressions of epithelial–mesenchymal transition‐associated factors were evaluated by Western blot. The expressions of RELA and TFAP2A were elevated in OSCC, and their expressions displayed a positive correlation. The expression levels of RELA and TFAP2A were found to be associated with TNM staging and lymphatic metastasis of OSCC patients. RELA upregulation promoted OSCC progression, as manifested by increased levels of proliferation, invasion, and migration of OSCC cells. We also demonstrated that RELA was directly bound to the promoter of TFAP2A transcription, which activated multiple malignant and metastatic phenotypes. Furthermore, TFAP2A activated the Wnt/β‐catenin signaling by targeting the promoter regions of β‐catenin. The study found that RELA is critical for promoting the progression of OSCC via the RELA‐TFAP2A‐Wnt/β‐catenin signaling pathway. The RELA‐TFAP2A‐Wnt/β‐catenin signaling pathway is a potential target for reducing the aggressiveness of OSCC.